Breeding in bambara groundnut (Vigna subterranea (L.) Verdc): strategic considerations - Massawe, F.; Nwale, S.; Azam-Ali, S.N.; Roberts, J. (Academic Journals, 2005)
Bambara groundnut (Vigna subterranea (L.) Verdc.) has a large number of landraces throughout Africa where small-scale farmers have preserved its genetic diversity on-farm. To date, the full genetic diversity of the crop remains largely unexploited. Until recently bambara groundnut never received any appreciable research effort, especially for its genetic improvement. Until then, only selection breeding was practised in which existing landraces were evaluated and their seeds multiplied. However, no new combinations resulting from hybridisation had ever been produced. Recently, collaborative research efforts involving partners from Africa and Europe have produced the first crosses of bambara groundnut. The creation of these crosses is a significant scientific and practical achievement and opens up the possibility of breeding true varieties of this crop. This paper shows how different strategies have been combined to establish the basis of a strategic breeding programme in bambara groundnut. The paper also illustrates the use of landraces in the bambara groundnut breeding programme, as an example of the contribution that landraces can make to increasing productivity in marginal environments and the conservation of a crop’s genetic resources on-farm.